CONVERSION OF 1,3-THIAZOLIDINES TO DIHYDRO-1,4-THIAZINE BY CHLORINOLYSIS - LEE, WS; MAH, HD; NAM, KD; KANG, SB (KOREAN CHEMICAL SOC, 1992)
The ring expansion of 1,3-thiazolidines 4 derived from beta-ketoacid derivatives to the corresponding dihydro-1,4-thiazines 1 by using the action of chlorine on 4 has been achieved. In the chlorinolysis unisolable sulfenyl chlorides 5 may be formed from chlorosulfonium ions 11 by beta-elimination involving carbonyl activated methylene hydrogens. Addition of sulfenyl chloride to the internal double bond appears to form probable thiiranium ions 14, which in turn gave 1 with loss of acidic proton. Imminium ions 15 could be hydrolyzed easily to give enol 8. As a side reaction, dihydrothiazine that was formed was further chlorinated to produce dichlorides 16 which were rearranged readily to the chloromethyl compounds 10.
Keywords: DIHYDRO-1,4-OXATHIINS